Time series : - Brockwell, Peter J (Springer, 2006)
This book is a systematic account of linear time series models and their application to the modelling and prediction of data collected sequentially in time. The aim is to provide specific techniques for handling data and at the same time to provide a thorough understanding of the mathematical basis for techniques. Both time and frequency domain methods are discussed, but the book is written in such a way that either approach could be emphasized.